FLAME ANALYSIS BY SELECTED METHODS IN THE FREQUENCY DOMAIN - Grądz, Żaklin; Klimek, Jacek; Kozak, Czesław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
Diagnostics of pulverized coal combustion can be carried out in the field of process monitoring and analysis of measurement data. The information about changes in the flame is presented in the form of time series, which can be analyzed in the time and frequency domain. The paper presents an analysis of signals of changes in the intensity of the flame glow during pulverized coal combustion using power spectral density. On the basis of the periodograms determined using the Welch method, it was possible to determine the frequency components present in the signal.